High-performance anti-aging thermoplastic colloidal particles and preparation method thereof
By using polyethylene resin as a base material and a multi-stage mixing, cooling, and strip granulation process, the weather resistance and flexibility issues of polyvinyl chloride granules were solved, resulting in the preparation of high-performance, anti-aging thermoplastic granules and improving the overall performance of the product.
Patent Information
- Application Number
- CN202411479585.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
AI Technical Summary
In existing granule preparation processes, polyvinyl chloride has poor weather resistance, is easily aged and yellowed by ultraviolet radiation, and has poor flexibility.
High-performance, anti-aging thermoplastic granules are prepared by using polyethylene resin as a base material, adding stabilizers, plasticizers, anti-aging agents and modifiers, and through multiple mixing and cooling strip granulation processes.
It improves the oxidation resistance, stability, aging resistance, heat resistance and wear resistance of the granules, extends their service life, enhances their flexibility and flame retardancy, and prevents aging.
Smart Images

Figure CN119307029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic preparation, in particular to a high-performance anti-aging thermoplastic granule and a preparation method thereof. Background Art
[0002] With the rapid economic development of various countries and the improvement of people's living standards, the demand for rubber particles in various countries will gradually increase, and my country's rubber particle market will develop rapidly. Therefore, it is very important to understand the research and development direction, equipment, technology and trends of rubber particle production technology at home and abroad for rubber particles to improve product technical specifications and market competitiveness. Thermoplastic elastomer (TPS) is a type of plasticized polymer material that has rubber elasticity at room temperature and can flow at high temperature. Its polymer chain is composed of plastic segment (hard segment) and rubber segment (elastic soft segment). The plastic segment is reversible and forms a physical "cross-linking point" at room temperature, which plays a role in restraining and reinforcing the macromolecular components. At high temperatures, the restraint force is lost and it becomes plastic; the rubber segment is a highly elastic segment with a large free rotation ability, which provides the material with elastic properties.
[0003] Among the existing colloid particles and their preparation processes, for example, an anti-aging PVC colloid particle and its preparation process with publication number CN113549285A, the technical scheme is as follows: it is composed of the following components: PVC, a plasticizer, a filler, and a stabilizer, wherein the stabilizer at least includes a modified titanium dioxide powder; the preparation process of the modified titanium dioxide powder comprises the following steps: step (1), dissolving nano titanium dioxide and illite powder in water, stirring for at least 1 hour, to obtain a complex A solution; dissolving polyacrylic acid in water, stirring for at least 10 minutes, to obtain a sodium polyacrylate solution; step (2) , the complex A solution and the sodium polyacrylate solution are mixed, ultrasonicated at 60-70°C for 0.5-1h, and then kept warm at 60-70°C for 2-4h to obtain a modified titanium dioxide mixed solution, and then dried to obtain a modified titanium dioxide powder. However, the existing raw material for preparing the hungry particles uses PVC, i.e., polyvinyl chloride, which is a polymer formed by the polymerization of vinyl chloride monomer in the presence of initiators such as peroxides and azo compounds or under the action of light and heat according to the free radical polymerization reaction mechanism. Polyvinyl chloride has poor weather resistance and is easily aged and yellowed by ultraviolet radiation, and has poor flexibility.
[0004] In view of this, we conducted in-depth research on the above issues, which led to the present case.
[0005] In view of the above problems, an innovative design is carried out on the basis of the original colloid particles and their preparation process. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance anti-aging thermoplastic rubber particle and a preparation method thereof, so as to solve the problems mentioned in the above background technology that polyvinyl chloride has poor weather resistance, is easily aged and yellowed due to ultraviolet radiation, and has poor flexibility.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A high-performance anti-aging thermoplastic granule. The raw materials for preparing the thermoplastic granule include a polyethylene resin base material, a stabilizer, a plasticizer, an anti-aging agent, and a modifier. The polyethylene resin base material is added with a stabilizer and a plasticizer, stirred, heated and mixed, extruded through an extruder, cooled through a water tank to form strips, cut into particles, added with an anti-aging agent and a modifier to the particles, stirred, heated and mixed again, extruded through an extruder, cut into particles again, dried through a dehydrator, cooled through a vibrating screen, and screened through a vibrating screen to obtain qualified products. The qualified products are stirred and dried through a stirring barrel.
[0009] Preferably, the raw material for preparing the thermoplastic particles comprises a polyethylene resin base material, and the polyethylene resin base material improves anti-aging performance.
[0010] By adopting the above technical scheme, polyethylene is used as the basic raw material for the production of thermoplastic particles. It has excellent moisture resistance and weather resistance. Compared with polyvinyl chloride, it can be exposed to the sun for a long time without aging and yellowing. Polyethylene has certain brittleness and low-temperature impact strength. In addition, polyethylene is not easy to absorb dyes or printing inks.
[0011] Preferably, the stabilizer comprises a light stabilizer and a heat stabilizer, and the light stabilizer comprises carbon black, zinc oxide and benzophenone, the carbon black and zinc oxide have a light shielding effect, and the benzophenone has an ultraviolet absorption effect.
[0012] By adopting the above technical solution, carbon black has a certain light shielding effect. By adding it into the raw material of thermoplastic particles, its stability is improved to prevent aging due to light. Zinc oxide is a relatively cheap catalyst that is easy to prepare and mass produce. Zinc oxide has good controllability and high stability, and can exert good catalytic performance under acidic or alkaline conditions.
[0013] Preferably, the heat stabilizer comprises 5% nano-montmorillonite, 10% nano-wollastonite and 5% synthetic mica, and the heat stabilizer improves the heat resistance of the polyethylene resin base material.
[0014] By adopting the above technical scheme, since the heat resistance of polyethylene raw materials is poor, the heat deformation temperature of the polyethylene raw materials can be increased from 70 degrees to 150 degrees by filling nano-montmorillonite in the additives, and the heat deformation temperature can be increased from 70 degrees to 160 degrees by filling nano-wollastonite, and the heat deformation temperature can be increased from 70 degrees to 145 degrees by filling synthetic mica, thereby effectively improving the heat resistance of the thermoplastic particles.
[0015] Preferably, the plasticizer comprises diphthalic acid, and diphthalic acid reduces the surface hardness of the thermoplastic particles.
[0016] By adopting the above technical scheme, the plasticizer adopts phthalic acid diisocyanate, which mainly weakens the secondary bonds between resin molecules, increases the mobility of resin molecular bonds, reduces the crystallinity of resin molecules, increases the plasticity of resin molecules, enhances their flexibility, and facilitates processing.
[0017] Preferably, the polyethylene resin base material is added with a stabilizer and a plasticizer, stirred, heated, mixed, and the extruded material is cooled through a water tank, and the cooled raw material is convenient for cutting after being drawn into strips.
[0018] By adopting the above technical scheme, the particles are cooled and stretched by underwater granulation, which improves the cooling efficiency and enhances the toughness of the thermoplastic particles, and is convenient for cutting into particles for secondary modification.
[0019] Preferably, the antioxidant comprises a hindered phenol antioxidant, a phosphite and a thioether, and the hindered phenol antioxidant shows a synergistic effect with auxiliary antioxidants such as phosphites and thioethers, and the hindered phenol antioxidant improves the antioxidant performance of the preparation of thermoplastic particles.
[0020] By adopting the above technical scheme, hindered phenol antioxidants cooperate with auxiliary antioxidants such as phosphites and thioethers to show a synergistic effect, effectively improving the antioxidant properties of the finished products prepared from thermoplastic particles.
[0021] Preferably, the antioxidant contains a free radical scavenger, and the free radical scavenger improves the stability of the thermoplastic particles.
[0022] By adopting the above technical solution, the free radical scavenger is a substance that can react with active free radicals that cannot exist stably for a long time and are generated during a chemical reaction to form free radicals or stable molecules that can exist stably for a long time.
[0023] Preferably, the modifier comprises glass fiber, and the glass fiber improves the toughness and wear resistance of the thermoplastic particles.
[0024] By adopting the above technical solution, adding glass fiber can make the plastic have higher rigidity and strength, making it more difficult to tear or break. At the same time, it can also improve the wear resistance of the plastic and extend its service life. At the same time, it can improve the flame retardancy and stability of the thermoplastic particles, and improve its chemical and UV resistance, effectively preventing the aging of the thermoplastic particles.
[0025] Preferably, the preparation method of the high-performance anti-aging thermoplastic particles is as follows:
[0026] Step 1: Add stabilizer and plasticizer to the polyethylene resin base material in an oil-filled mixing barrel and stir and mix;
[0027] Step 2: Extruding the mixed product in step 1 through a twin-screw extruder to produce the raw materials for making thermoplastic rubber particles;
[0028] Step 3: placing the extrudate in step 2 in a water tank for feeding, and cooling and water drawing the extruded raw materials on a water drawing production line;
[0029] Step 4: Cut the strip semi-finished product extruded in step 3 into individual pellets through a pelletizer;
[0030] Step 5: adding the anti-aging agent and the modifier to the colloid particles in step 4 again to mix, and repeating the operations of steps 2, 3 and 4;
[0031] Step 6: Use a dehydrator to spin dry the water out of the pellets;
[0032] Step 7: Use a vibrating screen to cool the pellets and screen out qualified pellets;
[0033] Step 8: Use a mixing barrel to dry the pellet product.
[0034] By adopting the above technical scheme, the raw materials and additives are mixed twice for cooling and stretching granulation, the thermoplasticity of the granules can be improved, and the oxidation resistance, stability, aging resistance, heat resistance and wear resistance of the granules can be improved, thereby producing high-performance thermoplastic granules that are helpful for the quality of automobile production.
[0035] Compared with the prior art, the invention has the following beneficial effects: the high-performance anti-aging thermoplastic particles and the preparation method thereof,
[0036] 1. The invention provides a method for adding an anti-aging agent to improve the performance of thermoplastic particles. The anti-aging agent includes a hindered phenol antioxidant, a phosphite and a thioether, and the hindered phenol antioxidant shows a synergistic effect with auxiliary antioxidants such as phosphites and thioethers, and the hindered phenol antioxidant improves the antioxidant performance of the preparation of thermoplastic particles. The anti-aging agent includes a free radical scavenger, and the free radical scavenger improves the stability of the thermoplastic particles. The hindered phenol antioxidant cooperates with auxiliary antioxidants such as phosphites and thioethers to show a synergistic effect, and effectively improves the antioxidant performance of the finished product prepared from the thermoplastic particles. The free radical scavenger is a substance that can react with active free radicals that cannot exist stably for a long time generated during a chemical reaction to form free radicals or stable molecules that can exist stably for a long time;
[0037] 2. The process of mixing raw materials and additives twice is repeated, and glass fiber is added for modification. The modifier contains glass fiber, and the glass fiber improves the toughness and wear resistance of the thermoplastic particles. The addition of glass fiber can make the plastic have higher rigidity and strength, making it more difficult to tear or break. At the same time, it can also improve the wear resistance of the plastic and extend its service life. At the same time, it can improve the flame retardancy and stability of the thermoplastic particles, and improve its chemical and ultraviolet resistance, effectively preventing the aging of the thermoplastic particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the structure of the preparation method of the present invention. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] See also Figure 1 , the present invention provides a technical solution:
[0041] A high-performance anti-aging thermoplastic granule. The raw materials for preparing the thermoplastic granule include a polyethylene resin base material, a stabilizer, a plasticizer, an anti-aging agent, and a modifier. The polyethylene resin base material is added with a stabilizer and a plasticizer, stirred, heated and mixed, extruded through an extruder, cooled through a water tank to form strips, cut into particles, added with an anti-aging agent and a modifier, stirred, heated and mixed again, extruded through an extruder, cut into particles again, dried through a dehydrator, cooled through a vibrating screen, cooled through a vibrating screen to select qualified products, and stirred and dried through a mixing barrel.
[0042] The raw materials for preparing thermoplastic particles include polyethylene resin base material, and the polyethylene resin base material improves anti-aging performance. As the basic raw material for the production of thermoplastic particles, polyethylene has excellent moisture resistance and weather resistance. Compared with polyvinyl chloride, it is not easy to age and turn yellow after long-term exposure to sunlight. Polyethylene has certain brittleness and low-temperature impact strength. In addition, polyethylene is not easy to absorb dyes or printing inks.
[0043] The stabilizer includes a light stabilizer and a heat stabilizer, and the light stabilizer includes carbon black, zinc oxide and benzophenone. Carbon black and zinc oxide have a light shielding effect, and benzophenone has an ultraviolet absorption effect. The heat stabilizer includes 5% nano-montmorillonite, 10% nano-wollastonite and 5% synthetic mica, and the heat stabilizer improves the heat resistance of the polyethylene resin base material. Carbon black has a certain light shielding effect. By adding it to the raw material for producing thermoplastic particles, its stability is improved to prevent aging due to light. Zinc oxide is a relatively cheap catalyst that is easy to prepare and mass-produce. Zinc oxide has good controllability and high stability, and can exert good catalytic performance under acidic or alkaline conditions. Since the heat resistance of polyethylene raw materials is poor, the heat deformation temperature of the additives can be increased from 70 degrees to 150 degrees by filling nano-montmorillonite, from 70 degrees to 160 degrees by filling nano-wollastonite, and from 70 degrees to 145 degrees by filling synthetic mica, which effectively improves the heat resistance of thermoplastic particles.
[0044] Plasticizers contain diphthalic acid, and diphthalic acid reduces the surface hardness of thermoplastic particles. The plasticizer uses diphthalic acid mainly to weaken the secondary bonds between resin molecules, increase the mobility of resin molecular bonds, reduce the crystallinity of resin molecules, increase the plasticity of resin molecules, enhance their flexibility, and make them easier to process.
[0045] The polyethylene resin base material is added with stabilizer and plasticizer, stirred, heated and mixed, and the extruded material is cooled through a water tank, and the cooled raw material is convenient for cutting after drawing. The particles are cooled and drawn by underwater granulation, which improves the cooling efficiency and enhances the toughness of the thermoplastic particles, and is convenient for cutting into particles for secondary modification.
[0046] The antioxidant includes hindered phenol antioxidants, phosphites and thioethers, and the hindered phenol antioxidants show synergistic effects with auxiliary antioxidants such as phosphites and thioethers, and the hindered phenol antioxidants improve the antioxidant properties of the preparation of thermoplastic particles. The antioxidant includes free radical scavengers, and the free radical scavengers improve the stability of thermoplastic particles. The hindered phenol antioxidants show synergistic effects with auxiliary antioxidants such as phosphites and thioethers, and effectively improve the antioxidant properties of the finished products prepared from thermoplastic particles. The free radical scavenger is a substance that can react with active free radicals that cannot exist stably for a long time generated during the chemical reaction to form free radicals or stable molecules that can exist stably for a long time.
[0047] The modifier contains glass fiber, and the glass fiber improves the toughness and wear resistance of the thermoplastic particles. Adding glass fiber can make the plastic have higher rigidity and strength, making it more difficult to tear or break. At the same time, it can also improve the wear resistance of the plastic and extend its service life. At the same time, it can improve the flame retardancy and stability of the thermoplastic particles, and improve its chemical and UV resistance, effectively preventing the aging of the thermoplastic particles.
[0048] The preparation method of high-performance anti-aging thermoplastic particles is as follows:
[0049] Step 1: Add stabilizer and plasticizer to the polyethylene resin base material in an oil-filled mixing barrel and stir and mix;
[0050] Step 2: Extruding the mixed product in step 1 through a twin-screw extruder to produce the raw materials for making thermoplastic rubber particles;
[0051] Step 3: placing the extrudate in step 2 in a water tank for feeding, and cooling and water drawing the extruded raw materials on a water drawing production line;
[0052] Step 4: Cut the strip semi-finished product extruded in step 3 into individual pellets through a pelletizer;
[0053] Step 5: adding the anti-aging agent and the modifier to the colloid particles in step 4 again to mix, and repeating the operations of steps 2, 3 and 4;
[0054] Step 6: Use a dehydrator to spin dry the water out of the pellets;
[0055] Step 7: Use a vibrating screen to cool the pellets and screen out qualified pellets;
[0056] Step 8: Use a mixing barrel to dry the pellet product.
[0057] By mixing the raw materials and additives twice and then cooling and stretching the pellets, the thermoplasticity of the pellets can be improved while the oxidation resistance, stability, aging resistance, heat resistance and wear resistance of the pellets can be improved, thereby producing high-performance thermoplastic pellets that are beneficial to the quality of automobile production.
[0058] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-performance anti-aging thermoplastic granule, characterized by: The raw materials for preparing the thermoplastic granules include polyethylene resin base material, stabilizer, plasticizer, anti-aging agent, and modifier. The polyethylene resin base material is added with stabilizer and plasticizer, stirred, heated and mixed, extruded through an extruder, cooled through a water tank to form strips, cut into particles, added with anti-aging agent and modifier to the particles, stirred, heated and mixed again, extruded through an extruder, cut into particles again, dried through a dehydrator, cooled through a vibrating screen, and qualified products are screened through the vibrating screen. The qualified products are stirred and dried through a stirring barrel.
2. The high-performance anti-aging thermoplastic granules according to claim 1, characterized in that: The raw materials for preparing the thermoplastic particles include a polyethylene resin base material, and the polyethylene resin base material improves the anti-aging performance.
3. The high-performance anti-aging thermoplastic granules according to claim 1, characterized in that: The stabilizer comprises a light stabilizer and a heat stabilizer, and the light stabilizer comprises carbon black, zinc oxide and benzophenone, the carbon black and zinc oxide have a light shielding effect, and the benzophenone has an ultraviolet absorption effect.
4. The high-performance anti-aging thermoplastic granules according to claim 3, characterized in that: The heat stabilizer comprises 5% of nano-montmorillonite, 10% of nano-wollastonite and 5% of synthetic mica, and the heat stabilizer improves the heat resistance of the polyethylene resin base material.
5. The high-performance anti-aging thermoplastic granules according to claim 1, characterized in that: The plasticizer includes diphthalic acid, and diphthalic acid reduces the surface hardness of the thermoplastic rubber particles.
6. The high-performance anti-aging thermoplastic granules according to claim 1, characterized in that: The polyethylene resin base material is added with a stabilizer and a plasticizer, stirred, heated, mixed, and extruded, and then cooled through a water tank. The cooled raw material is convenient for cutting after being drawn into strips.
7. The high-performance anti-aging thermoplastic granules according to claim 1, characterized in that: The antioxidant comprises hindered phenol antioxidant, phosphite and thioether, and the hindered phenol antioxidant shows synergistic effect with auxiliary antioxidants such as phosphite and thioether, and the hindered phenol antioxidant improves the antioxidant performance of the preparation of thermoplastic particles.
8. The high-performance anti-aging thermoplastic granules according to claim 7, characterized in that: The antioxidant contains a free radical scavenger, and the free radical scavenger improves the stability of the thermoplastic particles.
9. The high-performance anti-aging thermoplastic granules according to claim 1, characterized in that: The modifier contains glass fibers, and the glass fibers improve the toughness and wear resistance of the thermoplastic particles.
10. A method for preparing high-performance anti-aging thermoplastic particles, characterized in that: The preparation method of the high-performance anti-aging thermoplastic particles is as follows: Step 1: Add stabilizer and plasticizer to the polyethylene resin base material in an oil-filled mixing barrel and stir and mix; Step 2: Extruding the mixed product in step 1 through a twin-screw extruder to produce the raw materials for making thermoplastic rubber particles; Step 3: placing the extrudate in step 2 in a water tank for feeding, and cooling and water drawing the extruded raw materials on a water drawing production line; Step 4: Cut the strip semi-finished product extruded in step 3 into individual pellets through a pelletizer; Step 5: adding the anti-aging agent and the modifier to the colloid particles in step 4 again to mix, and repeating the operations of steps 2, 3 and 4; Step 6: Use a dehydrator to spin dry the water out of the pellets; Step 7: Use a vibrating screen to cool the pellets and screen out qualified pellets; Step 8: Use a mixing barrel to dry the pellet product.
Citation Information
Patent Citations
Anti-aging PVC (polyvinyl chloride) colloidal particle and preparation process thereof
CN113549285A